Studying the Influence of Cobalt Chloride on the Optical Properties of Poly (vinyl alcohol) Films - Hashim, Hassan; Abdallh, Mustafa; Yousif, Emad (Al-Nahrain Journal of Science, 2018)
The change in the optical band gap and optical activation energy have been investigated for pure and doped Poly (vinyl alcohol) with different cobalt chloride concentrations have been prepared to study their optical properties from the absorption spectra. The absorption spectra were measured in the wave range from (200-800) nm at room temperature. The optical band gap (Eg) for allowed direct transition decrease with increase the concentration of Cobalt Chloride. The optical activation energy for allowed direct transition band gap was evaluated using Urbach- edges method.